Avaliação do efeito antiflamatório e antinociceptivo do α- e ß-amirina, em modelo de doença periodontal e nocicepção orofacial em ratos - Pinto, Sergio Araújo Holanda (2008)
This study evaluated the triterpene pentaclycle α- ß-amyrin anti-inflammatory potential on the stages of periodontitis, acute and chronic, in rats. The periodontitis was induced through ligature placement around the second left upper molar. Rats (n=8) were treated with α, β-amyrin (5 and 10 mg/kg, v.o). Sham-operated and positive-controls (lumiracoxibe 20 mg/kg, v.o. and dexametasone, 1 mg/kg, i.p.) were included. The TNF-alfa levels in the plasma were evaluated and gingival tissues analyzed for myeloperoxidase (MPO) and thiobarbituric acid-reactive substances (TBARS). Both α, β-amyrin and dexametasone decreased the levels of TNF-alfa, MPO and TBARS. In chronic stage, the animals were observed and treated for a period of 11 days, in which the rats received the same drugs and were evaluated regarding their body mass variation and bone loss index, besides, were submitted to histopathological study of bone and gingival tissues. In the evaluation of the body mass variation, α, β-Amyrin and lumiracoxibe caused an increase in the weight gain, while a decrease occurred in rats treated with dexametasone when compared with the normal group (p<0.05). In relation to bone loss index, it was observed that α, β-Amyrin 5 mg/kg did not prevent bone loss, whereas a concentration of 10 mg/kg displayed an increase in bone loss; this increase also was perceived in the positive controls, lumiracoxibe and dexametasone, in relation to the sham-operated rats group (p<0.01). In conclusion, α, β-amyrin modulates acute phase periodontal inflammation and presents anti-inflammatory activity in both acute and chronic phases, but do not have the capacity to prevent bone loss. In parallel to this study, we also investigated the α, β-amyrin effect in model of orofacial pain induced in rats by formalin and capsaicin. The animals were pre-treated with α, β-amyrin (10, 30, and 100 mg/kg, i.p.), or vehicle (Tween 80, 3%), and than received either formalin (20 μl, 1.5%) or capsaicin (20 µl, 1.5 μg) injection into the vibrissa central right side. After data analysis, it was concluded that α, β-amyrin exerts antinociception effect in experimental model of orofacial pain.